The role of spatial ability in high school students’ understanding of molecular geometry - Ramadhan, Muhamad Farhan; Heliawati, Leny; Rubini, Bibin (Education and Development Research, 2025)
Molecular geometry is one of the biggest challenges in science education. Since molecular structures exist at a microscopic level, students often struggle to visualize them in three dimensions (3D), making it difficult to understand concepts such as bond angles, molecular shapes, and electron pair interactions. This study explores the role of spatial ability in high school students’ understanding of molecular geometry. Using a quantitative descriptive method, the study examined the spatial ability and molecular science comprehension of 58 high school students. Data were collected using standardized tests, including the Mental Rotation Test (MRT), shape assembly, and 3D visualization for spatial ability, along with a molecular science comprehension test focusing on VSEPR theory. The results obtain that students' spatial ability is significantly low, with average scores falling far below expected standard. The results suggest the need for more effective teaching strategies that incorporate 3D visualization tools to enhance students’ ability. Future research should focus on interactive learning approaches, such as virtual simulations to help students better visualize molecular structures and improve their understanding of science concepts.